1988
DOI: 10.1123/apaq.5.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Training Practices of Elite Wheelchair Roadracers

Abstract: This project assessed training behaviors and attributes of elite wheelchair racers. Training information was received from 36 participants in the 1985 National 10K Wheelchair Roadracing Championship. Data were obtained about age, weight, nature and level of disability, racing experience, sources of training information, level of cigarette and alcohol use, and dietary habits. Weekly training behaviors across yearly quarters were assessed with regard to the number of weekly pushing workouts, length of pushing wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Indeed, training practices of the SCI athletes in the present study (Table II) are similar to those previously reported for other elite wheel chair-dependent road racers. 1 The male SCI road racers elicited a significantly higher (by 18% ) peak V02 than the male able bodied group during maximal effort ACE exercise. It has been previously demonstrated that arm volume and arm strength contribute to ACE peak PO achieved by able bodied subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, training practices of the SCI athletes in the present study (Table II) are similar to those previously reported for other elite wheel chair-dependent road racers. 1 The male SCI road racers elicited a significantly higher (by 18% ) peak V02 than the male able bodied group during maximal effort ACE exercise. It has been previously demonstrated that arm volume and arm strength contribute to ACE peak PO achieved by able bodied subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Liow and Hopkins (1996) reported that many elite athletes with disabilities trained in ways that were not sport specific and they tapered poorly. Research by Watanabe et al (1992), finding some athletes overtrained on recovery days, and by Hedrick, Morse, and Figoni (1988), indicating athletes trained inconsistently, also suggests that athletes would benefit from improved coaching. Athletes have also reported a lack of availability of training material specific to their sport (Williams & Taylor, 1994).…”
Section: Facilitative Factorsmentioning
confidence: 91%
“…The study by Zoerink (1992) is the only one, however, that focuses specifically on the differential socialization of these two groups. Despite this limited attention, though, the adult socialization patterns reported among individuals with spinal cord injuries or amputations by Kennedy (1980), Hopper (1982, and Hedrick et al (1988) are manifestly different from the childhood and adolescent patterns of those with cerebral palsy reported by Shemll, Rainbolt, Montelione, and Pope (1986) or those with hearing impairments reported by Stewart et al (1988Stewart et al ( , 1991.…”
Section: Personal Attributesmentioning
confidence: 93%
“…This is further supported by two studies that did not study an impairment group but rather elite athletes who participate in wheelchair sports. Hedrick, Morse, and Figoni (1988) examined the training practices of wheelchair racers and sources from which they obtained relevant information; the authors found "other athletes" and "magazines" to be the primary sources. Parents and teachers made no contribution, and this was corroborated in a replication of Hedrick et al's (1988) study undertaken by Watanabe, Cooper, Vosse, Baldini, and Robertson (1992).…”
Section: Significant Othersmentioning
confidence: 99%
See 1 more Smart Citation